Traditional Knowledge of Banyumas Community about Mesua ferrea as the Identity Plant - Enni Suwarsi Rahayu; Erni Suharini; Siti Fathonah; Aisirotul Maisah (Biosaintifika: Journal of Biology & Biology Education, 2020)
The population of Mesua ferrea L. in Banyumas Regency, Central of Java Province is very low. There are some factors affecting the quantity of plant population, particularly traditional knowledge of local community about the plant. The aim of this study was to describe the knowledge of Banyumas community about the existence, economic value, usefulness, and propagation technique of M. ferrea. The study was done by field survey on a total of 146 residents from 10 districts which were determined by proportionally stratified random sampling. Data obtained from questionnaires and interviews were analyzed by percentage descriptive. The results revealed that only 9% of respondents were familiar with the M. ferrea and knew its status as plant identity of Banyumas Regency. Most of the respondents did not understand the economic value, only 8% of respondents understood the usefulness, 2% of respondents had utilized the timber as craft material, and 3% understood the propagation technique. The utilization was very low, equal to 14.45% compared to the potential usefulness. Most of the respondents (98%) thought that conservation efforts should be undertaken. This study found that the traditional knowledge of M. ferrea in Banyumas was low. This result should be used as a basic information for developing conservation program of M. ferrea. Â